Validitas RPP Model Discovery Learning pada Mata Pelajaran Matematika di SD - Nabila, Ni’matul (Program Studi Akuntansi IKOPIN, 2022)
This research is motivated by educators who force students without first paying attention to the needs, interests and talents of their students. They never give students the opportunity to find something and explore their potential. The results of the 2015TIMMS for grade IV elementary schools, Indonesia got an average score of 397 and was ranked in the bottom 4 of the 43 countries that participated in the TIMMS (Source: TIMMS 2015 International Database). About 75% of the items tested in TIMSS have been taught in grade V elementary school and this is higher than South Korea which is only 68%, but the depth of understanding is still lacking in terms of the length of learning for elementary school students and the number of hours of Mathematics lessons, Indonesia is the most compared to other countries, but the quality of learning still needs to be improved. RPP is a plan for describing procedures and teaching management to achieve one or more basic competencies set out in competency standards and outlined in the syllabus. Prior to learning, you must use a learning model that is in accordance with the characteristics of students, namely using the Discovery Learning learning model. To ensure the quality of the lesson plans, a special study is needed to assess the validity. This study aims to assess aspects of the validity of the lesson plan. This research is a descriptive quantitative research that presents the data from the validation results and the validator's suggestions on the validity of the lesson plans. The validator consists of two people, namely a lecturer at PGRI Adi Buana University Surabaya and the other a fifth grade teacher at SDN in the city of Mojokerto. The instrument used is the lesson plan model of Discovery Learning. The results of the analysis of the validation sheet show that in general the lesson plans meet the valid criteria.